THE URGENCY OF SUI GENERIS PROTECTION OF COMMUNAL INTELLECTUAL PROPERTY IN INDONESIA: A Comparative Study in Philippines - Yenny Eta Widyanti (Jurisdictie: Jurnal Hukum dan Syariah, 2022)
Indonesia is a culturally megadiverse country, which is a source of Communal Intellectual Property. However, Communal Intellectual Property that has high economic value can lead to the misappropriation and destruction instigated by foreign parties. Thus, a Communal Intellectual Property legal protection is needed in the international and national law. This research aims to describe about communal intellectual property in national and international law. By using normative juridical research, statute approach, conceptual approach, and comparative approach regarding primary and secondary legal materials, it is then analyzed with the findings that Communal Intellectual Property protection in international and national law do not only cover legal protection in the field of Intellectual Property Rights. It also encompasses nonIntellectual Property Rights legal protection, both preventively and repressively (hybrid protection). This research has an essential meaning in the formation of national law on sui generis Communal Intellectual Property by adopting the best practices in the Philippines.Indonesia adalah negara yang kaya dengan keanekaragaman budaya, sebagai sumber Kekayaan Intelektual Komunal. Namun, dalam perkembangannya, Kekayaan Intelektual Komunal yang memiliki nilai ekonomi tinggi menjadi potensi penyalahgunaan dan perusakan oleh pihak asing, sehingga diperlukan perlindungan Kekayaan Intelektual Komunal dalam hukum internasional dan hukum nasional yang memadai. Penelitian ini bertujuan untuk memaparkan perlindungan Kekayaan Intelektual Komunal dalam hukum nasional dan internasional. Dengan menggunakan jenis penelitian yuridis normatif dan pendekatan peraturan perundangan, pendekatan konseptual, serta pendekatan perbandingan dari bahan hukum primer dan bahan hukum sekunder, maka kemudian dianalisis dengan temuan bahwa perlindungan Kekayaan Intelektual Komunal dalam hukum internasional dan hukum nasional tidak cukup hanya dengan perlindungan hukum di bidang Hak Kekayaan Intektual, namun juga meliputi perlindungan hukum non Hak Kekayaan Intelektual baik secara preventif maupun represif (perlindungan campuran). Penelitian ini memiliki arti penting dalam pembentukan hukum nasional Kekayaan Intelektual Komunal secara sui generis dengan mengadopsi praktik terbaik di Filipina.